Diseño de Mobiliario en Fibra de Vidrio para espacios Lounge - Cepeda Cárdenas, Carlos Eduardo (2025)
The thesis entitled “Design of fiberglass furniture for lounge spaces” proposes the development of innovative furniture that integrates aesthetics, functionality and durability, aimed at the lounge sector. This project originates as a response to the diversification needs of the Masterfibra company, with the aim of improving its competitiveness in national and international markets. The document examines the technical properties of fiberglass, the main material to be used, highlighting its resistance, flexibility and its ability to adapt to different designs. In addition, an exhaustive analysis of market trends, consumer needs and quality standards applicable to lounge furniture is carried out. Thanks to a methodological approach that combines conceptual design, prototype manufacturing and evaluation of results, products have been created that meet high standards of ergonomics and functionality. Likewise, the project presents a solid theoretical framework that underlines the importance of industrial design and the competitive advantages offered by fiberglass in the creation of furniture. A context analysis is carried out, highlighting both the opportunities and challenges facing the industry. This thesis presents innovative solutions that not only satisfy the needs of customers, but also position masteribra as a reference in design and in the field of furniture.